2007
DOI: 10.1164/rccm.200611-1598oc
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell Apoptosis in Obstructive Sleep Apnea

Abstract: In patients with OSA, impairment of endothelial-dependent vasodilation correlated with the degree of endothelial cell apoptosis. CPAP therapy led to significant decline in circulating apoptotic endothelial cells. These findings provide an additional mechanism for the predisposition of patients with OSA to premature vascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
2
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(103 citation statements)
references
References 41 publications
6
90
2
5
Order By: Relevance
“…In the current study, we did not characterize the state of activation or viability of the CECs or EPCs, Recently, El Solh et al [29] reported a significant increase in the number of CD146-positive and annexin V-positive cells in patients with OSA. The authors concluded that apoptotic CECs are increased in OSA.…”
Section: Discussionmentioning
confidence: 68%
“…In the current study, we did not characterize the state of activation or viability of the CECs or EPCs, Recently, El Solh et al [29] reported a significant increase in the number of CD146-positive and annexin V-positive cells in patients with OSA. The authors concluded that apoptotic CECs are increased in OSA.…”
Section: Discussionmentioning
confidence: 68%
“…Numerous studies noted that flow-mediated dilation, measured locally in the brachial artery, was decreased in OSA patients compared with non-OSA controls, 2,53,[65][66][67] indicating that endothelial dysfunction occurs in OSA. However, here we discuss the available literature that furthers our understanding of the effect of OSA on arterial function, showing that not only local, but also global arterial function is impaired in OSA.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7] Arterial stiffness is independently associated with cardiovascular risk [19][20][21][22][23][24]26,[28][29][30][31][75][76][77][78] and may therefore provide a potential explanation for the increased risk of cardiovascular events in OSA patients. Furthermore, a strong correlation between arterial stiffness and the development of atherosclerosis at various sites in the arteries has been noted.…”
Section: Therapeutic and Clinical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several experimental and clinical studies have shown that nocturnal hypopnea induces increases in blood pressure levels 6,19 and the progression of arterial stiffness. 18,19 Endothelial dysfunction 4,[20][21][22] and disturbances of sympathetic activity 5,23 are recognized clinical features in OSA patients that increase vascular tone and accelerate the progression of arterial stiffness. 7 Chronic intermittent hypoxia causes dyslipidaemia and initiates the development of atherosclerosis, both of which contribute to arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%